Palimpsestuous reading of Josep Palau i Fabre, logophagus - Sullà, Enric (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Amongst the figures of logophagy that Túa Blesa puts forward in his remarkable Logografías (1998), there is the text-apsis. The article states that «L’aventura», by Josep Palau i Fabre, a sequence of five poems of eight lines each, is a text-apsis, although differing from the figure, because has an original to refer to «Sensation», by Arthur Rimbaud. If the first sequence of Palau’s poem is a fairly faithful translation of the French original, the following four become more and more an original poem by Palau. The article offers a close reading of Palau’s Catalan and Spanish version of his poem —translated and recreated by the poet himself— always related to Rimbaud’s poem —palimpsestuous-ly—.
Keywords: Túa Blesa; logofagy; text-apsis; close reading; Arhur Rimbaud; «Sensation»; Josep Palau i Fabre; «L’aventura»; translation; version; recreation; selftranslation; Gérard Genette; palimpsestuous reading